Interrelation of Spiritualism and Materialism of Madrasah Teachers - Susmiyati, Sri; Zurqoni, Zurqoni; Saugi, Wildan; Dewi, Lharasati; Abdillah, Muhamad Hasan (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
While materialism is strongly spreading in society, one of which is in the educational environment, madrasah teachers are supposed to have high spiritualism to be able to control it. This research aims to analyze the interrelation of spiritualism and materialism of madrasah teachers in East Kalimantan. The research used a quantitative-correlative approach with 1604 madrasah teachers in East Kalimantan as the research population. The selected sample, 241 State Madrasah Aliyah teachers, was taken using a purposive sampling technique. Data was collected using a questionnaire instrument, which was then analyzed using linear regression correlation analysis techniques. The research results show that there is a very significant relationship between spiritualism and materialism of madrasah teachers. The higher the teacher's spiritualism, the lower the materialism, conversely the lower the spiritualism, the higher the teacher's materialism. This research has implications for the importance of building the spiritualism of madrasah teachers so that they are not easily influenced by the strong materialism in the current era.